Exchange Rate Volatility and Aggregate Exports: Evidence from Two Small Countries. (4th December 2013) - Serenis, Dimitrios; Tsounis, Nicholas
Abstract : This paper examines the effect of exchange rate volatility for two small countries, Croatia and Cyprus, on aggregate exports during the period of first quarter of 1990 to first quarter of 2012. It is claimed by some researchers that exchange rate volatility causes a reduction on the overall level of trade. Empirical researchers often utilize the standard deviation of the moving average of the logarithm of the exchange rate as a measure of exchange rate fluctuation. In this study, we propose a new measure for volatility. Overall, our results suggest that there is a positive effect of volatility on exports of Croatia and Cyprus.